Speed Control of Three Phase Induction Motor using PI Controller with Space Vector Width Modulation (SVPWM) Technique - Iswadi Hasyim Rosma; Amir Hamzah; A. Ludfi Nur Kasan; Abubakar Abdulkarim; Sobhy Abdelkader (Journal of Applied Materials and Technology, 2022)
This article aimed to design and simulated the speed control of a three-phase induction motor using a PI controller with Space Vector Pulse width modulation technique. The induction motor  used in this article is was designed at the Electrical Energy Conversion Laboratory, Riau University, with a power of 1.1 kW, 380 V, 2-pole. Meanwhile, the PI controller constants used in designing this induction motor were determined using the Fine Tunning method to obtain KP and KI values of 3.539 and 9.526, respectively. The tests were carried out by running simulations in three conditions, namely no load, full load, and variable load at a speed of 2800 rpm. The test results showed that the use of a PI controller can improve the speed response of induction motors by eliminating the steady state error. This is in addition to increasing the rise time response of the motor speed by 0.012s and 0.046s at no load and full load, respectively, when the rise time analysis is at the same value. It can also accelerate the motor to reach a peak speed of 0.247 s and 0.166s at no load and full load. In addition, SPVWM with PI controller can maintain speed setting even though there is a load change during operation, which can be verified with load testing.